Pengaruh CR dan DER terhadap ROA pada Perusahaan Kosmetik dan Barang Keperluan Rumah Tangga - Henna Ardhefani; Rosma Pakpahan; Tjetjep Djuwarsa (Indonesian Journal of Economics and Management, 2021)
The aim of this research are to know the effect of CR and DER to ROA on companies subsector of cosmetics and household listed on Indonesia Stock Exchange Period 2012 - 2019. The research method used is quantitative descriptive method. The data used are secondary data in the form of annual financial reports. This research used purposive sampling method and obtained 5 samples of companies subsector of cosmetics and households listed on Indonesia Stock Exchange Period 2012 - 2019. Analytcal techniques used are classical test assumptions and multiple linear regression hypothesis test using partial T test and F test simultaneously at the significance level of 5% with SPPS version 26. This research showed partially CR is not having significant effect on ROA, and DER has a positive and significant effect on ROA. Therefore, simultaneously that CR and DER have a significant effect on ROA.